The Influence of Content Creator and Recommendation Algorithms on Gen Z’s Purchase Decision for Facetology Skincare Products on TikTok - Fannya Azzahra Assirayatul; Syamsul Bachri; Zakiyah Zahara; Moh. Ali Murad (Dinasti Publisher, 2025)
This study aims to explore how content from creators and recommendation algorithms influence Generation Z's purchasing decisions for Facetology skincare products on the TikTok platform. The method used is a descriptive quantitative approach involving 102 female respondents aged 15–28 years. Data analysis was performed using SPSS version 16, including validity and reliability tests, multiple linear regression, F-tests, and t-tests. The findings show that simultaneously and partially, creator content and recommendation algorithms have a positive and significant impact on purchasing decisions, with an Adjusted R² value of 0.538. The highest indicator in the creator content variable was “easy-to-understand language,” which demonstrated Tasya Farasya's ability to use communicative, clear, and relatable language to make it easy for the audience to understand product information and build trust in her recommendations. Meanwhile, in the recommendation algorithm variable, the highest indicator was “flexibility,” which reflected TikTok's ability to tailor content to user preferences. These factors encourage Generation Z to increase their purchasing decisions for recommended skincare products. This study emphasizes the importance of a collaborative strategy between creator credibility and algorithmic intelligence in shaping digital purchasing behavior among young consumers.